Derivation of sediment Hg quality standards based on ecological assessment in river basins. (February 2019) - Méndez-Fernández, Leire; Casado-Martínez, Carmen; Martínez-Madrid, Maite; Moreno-Ocio, Iñigo; Costas, Noemí; Pardo, Isabel; Rodriguez, Pilar
Abstract: The Environmental Quality Standards (EQS) directive was an important improvement of long-term water quality monitoring at the European level, leading to the use of sediments and biota as relevant matrices for assessing priority substances under the European Water Framework directive. Currently, commonly accepted sediment EQS for Hg are missing in Europe. In this study we present a new, tiered approach to deriving sediment quality standards for Hg: the derivation of Predicted No-Effect Concentration (PNEC) from data in the literature, followed by adjusting values at regional scale, using ecological field data (macroinvertebrate community assessment) and field sediment ecotoxicity bioassays. The limited set of effect data available for Hg spiked-sediment ecotoxicity tests has resulted in unreliable PNEC values for sediment quality assessment. Field reference sites (n = 40) where the macroinvertebrate community status was assessed as High or Good were used to define the ecological background and threshold levels in sediments in northern Spain. Sediment QS developed in other areas were not suitable for specific basins in our study area, since they were within the range of our Hg background levels. Temporary sediment Quality Standards (QS) for Hg were developed for the Nalón River basin (where several mining districts occur), using field effect-based approaches such as sediment ecotoxicity data from Tubifex tubifex chronic bioassays and ecological assessment of macroinvertebrate communities. A proposal for Hg quality assessment in freshwater sediments of northern Spain is made based on ecologically relevant QS values, providing benchmark values for No-Effect and Effect Hg sediment concentrations. Graphical abstract: Highlights: Derived sediment Hg PNECs are not reliable in due to limited data. Ecological background and threshold Hg levels are defined on field biological data. Ecological background Hg sediment levels in North Spain are mostly <0.5 mg kg −1 dw. Hg ecological threshold sediment levels in North Spain range from 0.49˗1.21 mg kg −1 dw. HC50 estimated from the SSD model with sensitive taxa abundances is 0.90 mg kg −1 dw. Abstract : Sediment quality standards for Hg are developed using background and threshold levels in sites with Good or High ecological status, and a classification is proposed based on Hg sediment levels associated with increasing risk of ecotoxicity and macroinvertebrate community alteration.